The Relationship Between Mother's Knowledge and Handling of Fever Seizures in Children aged 1-5 years in Central Village, Pancur Batu District in 2020 - Imelda Sirait; Linda Tampubolon; Ance Siallagan; Jagentar Parlindungan Pane; Tisep Fazryanti Telaumbanua (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2021)
Febrile convulsion often found in children 3-5 years old. This problem is a seizure that occurs when the body temperature rises and is caused by the extracranium process. This research was to decide the relationship between mother’s knowledge and management of febrile convulsion in children 1-5 years old in the Tengah village of Pancur Batu district 2020. This research is a cross-sectional study. We used to simple random sampling technique with 30 respondents. We used a questionnaire for the instrument. The final results showed that the majority of mother's knowledge regarding the management of febrile seizures was in the good category (86.7%) and the majority of febrile seizure management was in the category (90.0%). The results of chi-square statistical test show there is a relationship between knowledge of the mother with the handling of febrile seizures in children in the Tengah village of Pancur Batu District in 2020 (p value = 0,039). This study is expected to be an alternative for health workers to increase the promotion and prevention of problems related to the first treatment of febrile seizures. A person's knowledge is a factor that can influence a mother to take action, the better the mother's knowledge of diseases or health problems, the better the handling and vice versa, if the mother's knowledge is less, the handling of health problems will be better. Health education to the community will be a means to increase knowledge about handling health problems in the community.